Principles of Legal Settlement in Sharia Contracts - Rizka Syafriana (Randwick International of Social Science Journal, 2022)
Contracts in Fiqh Law have several terms, the focus of which is on a complete understanding of the concept of contract (al-'aqd). The term al-'aqd is defined as an agreement or contract in Islamic civil law. The contract referred to here is the nature of the given syarak for the contract based on the fulfillment of the pillars and their conditions, so that resolving the dispute problem can be done using Litigation (Religious Court) or by non-litigation. The Religious Courts are Case Settlement Institutions if there is a dispute in this Sharia contract which is detrimental to one of the parties.